نموذج التعليم الافتراضي لمهارة الكلام بالمدرسة الثانوية الحكومية الثانية مدينة مالانج في عصر جائحة كورونا - Reni Lailina Hidayah; Zakiyah Arifa (Prosiding Konferensi Nasional Bahasa Arab, 2021)
The purpose of this study is to describe the virtual learning model of speaking skills as well as the supporting and inhibiting factors. This study uses a qualitative method. The primary data sources in this study were the Arabic language teacher and class XI students. Secondary data sources are images, audio, and portfolios. Collecting data using guided interviews, virtual observation, and documentation. Data analysis using Milles and Huberman method. The results of this study are (1) learning speaking skills using zoom, WhatsApp, and youtube. The teacher applies 2 kinds of virtual learning, namely synchronous learning and asynchronous learning, with the question and answer method and the conversation method (2) while the supporting factors for this learning model are reducing monthly fees for students, having smartphones and internet networks, utilizing various learning media, student learning motivation. As for the inhibiting factor is the unstable internet signal, the task is too much.Keywords: Learning Model, Virtual Learning, Speaking Skills